Bigger than life - Roueché, Berton 1911-1994; Raksin, David 1912-2004 (<<The>> Criterion Collection, 2010)
A friendly schoolteacher turns violent when he becomes addicted to an experimental painkiller he is prescribed for a painful health problem.
Aspect ratio 2.55:1, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.: USA 1956
Enth. audio commentary featuring critic Geoff Andrew ("The Films of Nicholas Ray") ; "Profile of Nicholas Ray" (1977), a half-hour television interview with the director ; new video appreciation of "Bigger than life" with author Jonathan Lethem (Chronic City) ; new video interview with Susan Ray, widow of the director and editor of "I was interrupted: Nicholas Ray on Making Movies" ; a booklet featuring an essay by critic and video maker B. Kite
Keywords: Lehrer; Cortisone -- Drama.; Fathers and sons -- United States -- Drama.; Families -- United States -- Drama.; Teachers -- United States -- Drama.; Drug addicts -- United States -- Drama.; Feature films.; Melodramas (Motion pictures); Drogenabhängiger; Cortison; Vater; Familie; Melodrama -- Film; Sohn; USA; Film; DVD-Video